2012
DOI: 10.1021/tx3000494
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Hydrogen Transfer Reactions of Thiyl Radicals from Glutathione: Formation of Carbon-Centered Radical at Glu, Cys, and Gly

Abstract: Glutathione thiyl radicals (GS•) were generated in H2O and D2O by either exposure of GSH to AAPH#, photoirradiation of GSH in the presence of acetone, or photoirradiation of GSSG. Detailed interpretation of the fragmentation pathways of deuterated GSH and GSH-derivatives during mass spectrometry analysis allowed us to demonstrate that reversible intramolecular H-atom transfer reactions between GS• and C-H bonds at Cys[αC], Cys[βC], and Gly[αC] are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Theoretical calculations by Rauk and coworkers suggested that HAT reactions occur between thiyl radicals and the α C–H bonds of amino acids located in random and β-sheet conformations, but these do not occur when amino acids are located in α-helices [43]. Experimentally, the inter- and intramolecular HAT reactions of thiyl radicals have been demonstrated for amino acids, amino acid derivatives and peptides, including glutathione, in solution and in the gas phase [19,44,45,46,47,48,49,50]. Importantly, these HAT reactions do not only target α C–H bonds but also C–H bonds of amino acid side chains [51,52].…”
Section: Thiyl Radicals In Reversible Hat Reactionsmentioning
confidence: 99%
“…Theoretical calculations by Rauk and coworkers suggested that HAT reactions occur between thiyl radicals and the α C–H bonds of amino acids located in random and β-sheet conformations, but these do not occur when amino acids are located in α-helices [43]. Experimentally, the inter- and intramolecular HAT reactions of thiyl radicals have been demonstrated for amino acids, amino acid derivatives and peptides, including glutathione, in solution and in the gas phase [19,44,45,46,47,48,49,50]. Importantly, these HAT reactions do not only target α C–H bonds but also C–H bonds of amino acid side chains [51,52].…”
Section: Thiyl Radicals In Reversible Hat Reactionsmentioning
confidence: 99%
“…24−29 A pair of CysS • can also be generated through the direct photolysis of cystine (reactions 3). 26 −30 Our recent studies on the reactivity of CysS • radicals in peptides and proteins, including IgG1 and IgG2, have shown a pronounced tendency of CysS • to reversibly and selectively abstract hydrogen atoms from adjacent amino acids, from both the α C−H and side chain C−H bonds (equilibrium 4). 3,31 In a model peptide containing the sequence -Ala-CysAla-, such hydrogen transfer reactions resulted in the conversion of L-Ala into D-Ala, i.e., epimerization of the peptide sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we generated the biologically relevant thiyl radicals from glutathione and cysteine, abbreviated as and , respectively, to monitor their reaction with the and HE probes. One should note that and exist in equilibrium with their carbon-centered radicals as reported by Schöneich and coworkers 41 . Although this equilibrium is shifted to the side of the sulfur-centered radicals and is rather fast 42 , it may affect the reaction kinetics, and thus the determined rate constants should be treated as the “apparent” values.…”
Section: Resultsmentioning
confidence: 61%